Circulating CitH3 Is a Reliable Diagnostic and Prognostic Biomarker of Septic Patients in Acute Pancreatitis - Pan, Baihong; Li, Yaozhen; Liu, Yu; Wang, Wei; Huang, Gengwen; Ouyang, Yang (Frontiers in Immunology, 2021)
Purpose Acute pancreatitis (AP) is an inflammatory disease. AP starts with sterile inflammation and is often complicated with critical local or systemic infection, or sepsis in severe cases. Septic AP activates peptidyl arginine deiminase (PAD), citrullinated histone H3 (CitH3), leading to neutrophil extracellular traps (NETs) formation. Investigating the role of NETs and underlying mechanisms in septic AP may facilitate developing diagnostic and therapeutic approaches. In this study, we sought to identify the expression of CitH3 in septic AP patients, and to analyse the correlation of CitH3 concentration with NETs components as well as clinical outcomes. Methods 70 AP patients with or without sepsis (40 septic cases, 30 non-septic cases) and 15 healthy volunteers were recruited in this study. Concentration of NETs components (CitH3 and double strain DNA) and key enzymes (PAD2/4) were measured. Clinical and laboratory characteristics of patients were recorded and analyzed. Results Levels of CitH3 were elevated significantly in septic AP patients compared with non-septic AP and healthy volunteers. The area under curve (AUC, 95% CI) for diagnosing septic AP was 0.93 (0.86-1.003) and cut-off was 43.05 pg/ml. Among septic AP cases (n=40), concentration of CitH3 was significantly increased in those who do not survived or were admitted in intensive care unit, when compared with those who survived or were not admitted in intensive care unit. Association analysis revealed that CitH3 concentration was positively correlated with PAD2, PAD4, dsDNA concentration and Sequential Organ Failure Assessment scores. Conclusion CitH3 concentration increased in septic AP patients, and closely correlated with disease severity and clinical outcomes. CitH3 may potentially be a diagnostic and prognostic biomarker of septic AP.